Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2024)
Table of Content: 1. Vulnerability to the climate cycle and Assessing its effects on vegetation in Saudi Arabia A Case Study of the Prince’s Reserve Mohammed bin Salman Reserve Mr. Abdulla Ahmed Alabdali 2. The general situation of COVID-19 in Iraq Asst-Prof. Eman Mohammed Hussain, Asst-Prof. Hussein Kamil Awad, Asst-Prof. Emam Atiyah Ibadi 3. Comparison of the production performance of some phenotypic groups and their crosses of quail birds Asst-Prof. Esraa Mobasher Tawfeq